PENGARUH BAHAN AJAR BERORIENTASI MODEL PEMBELAJARAN KOOPERATIF EXAMPLES NON EXAMPLES TERHADAP HASIL BELAJAR IPA SISWA KELAS VIII SMP NEGERI 16 KERINCI - Synthatrisma Utami; Asrul Asrul; Yurnetti Yurnetti (PILLAR OF PHYSICS EDUCATION, 2015)
Learning science problem in junior high school is lack of students understanding towards physics concept because limited examples of the application of the concepts explained by the teacher. Therefore, researchers are trying to look at the influence of learning materials oriented cooperative learning models examples of non examples to the learning outcome of the students in grade VIII of SMP Negeri 16 Kerinci. The type  research  is quasi-exsperimental research and design is randomized control group only design. The population of the research was all students grade VIII in SMP Negeri 16 Kerinci which consists of four local. Sample was selected by applying cluster random sampling technique. The research data a learning outcome in cognitive aspect and affective aspect. The data was analyzed by hypothesis test by equality test of two averages which use t test. This research conclude that there is influence of learning materials oriented cooperative learning models examples of non examples to the learning outcome of the students in grade VIII of SMP Negeri 16 Kerinci for cognitive and affective aspect at significance level 5%